Crystal structure, spectroscopic measurement, optical properties, thermal studies and biological activities of a new hybrid material containing iodide anions of bismuth(iii). Issue 58 (24th September 2020) - Ben Ali, Saida; Feki, Amal; Ferretti, Valeria; Nasri, Moncef; Belhouchet, Mohamed
Abstract : A novel halogenobismuthate(iii ) organic–inorganic hybrid material named bis(4, 4′-diammoniumdiphenylsulfone) hexadecaiodotetrabismuthate(iii ) tetrahydrate, (C12 H14 N2 O2 S)2 [Bi4 I16 ]·4H2 O, has been prepared by slow evaporation at room temperature. Abstract : As part of our interest in halogenobismuthate(iii ) organic–inorganic hybrid materials, a novel compound named bis(4, 4′-diammoniumdiphenylsulfone) hexadecaiodotetrabismuthate(III) tetrahydrate with the chemical formula (C12 H14 N2 O2 S)2 [Bi4 I16 ]·4H2 O, abbreviated as (H2 DDS)[Bi4 I16 ], has been prepared by a slow evaporation method at room temperature. This compound was characterized by single crystal X-ray diffraction (SCXRD), spectroscopic measurements, thermal study and antimicrobial activity. The examination of the molecular arrangement shows that the crystal packing can be described as made of layers of organic [C12 H14 N2 O2 S] 2+ entities and H2 O molecules, between which tetranuclear [Bi4 I16 ] 4− units, isolated from each other, are inserted. The cohesion among the different molecules is assured by N–H⋯I, N–H⋯O and O–H⋯I hydrogen bonding interactions, forming a three-dimensional network. Room temperature IR, Raman spectroscopy of the title compound were recorded and analyzed. The optical properties were also investigated by both UV-vis and photoluminescence spectroscopy. Moreover, the synthesized compound was also screened for in vitro antimicrobial (Gram-positive and Gram-negative) and antioxidant activities (scavenging effect on DPPH free radicals, reducing power and total antioxidant capacity).